Evaluation of factors influencing the behavior of young mothers on the baby food market - A. Suszek-Namroży; R. Zabrocki (Scientific Journal of Gdynia Maritime University, 2017)
The aim of this study was to evaluate the factors influencing the behavior of young mothers on the baby food market. It was found that 87% of women use the ready meals for babies.